Implementasi Augmented Reality Stunting untuk Kader Aisyiyah Kota Cimahi - Suharjanto Utomo; Samsul Budiarto; Iswanto Iswanto; Indiraki Ramdhani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Regional Leadership of Aisyiyah Cimahi City has a new and excellent programme called “Cimahi City Zero Stunting to Welcome the Golden Generation” to assist the Cimahi government programme in reducing stunting rates. Aisyiyah stunting cadres in Cimahi city need to increase their capacity in understanding stunting, an approach with information technology is expected to be easier and more interesting. Augmented reality (AR) is a technology that combines the real world with digital or virtual elements generated, thus creating an interesting and interactive user experience. By implementing Augmented Reality in the form of Stunting education media, it is hoped that it will increase the understanding of Aisyiyah cadres in Cimahi city. The application developed can be run on an android phone so that it can be easily used by stunting cadres and the community.